Assessing Student Orientation to School to Address Low Achievement and Dropping Out (Alberta Journal of Educational Research, 2015)
This study contributes to applied and theoretical research for schools and districts by helping inform programs and policies directed at school improvement, raising student achievement, and high school completion. The paper features recent results of ongoing research on student orientation to school that was assessed via a multi-dimensional Student Orientation to School Questionnaire (SOS-Q). The SOS-Q was initially used by a Canadian school district to better understand the reasons for dropping out of school. Since then the project has grown into a multi-organizational collaboration. This study demonstrates persistent associations between student orientation to school, academic achievement, and high school completion and makes the case for integrating valuable non-cognitive components within comprehensive student information and assessment systems.Cette étude contribue à la recherche appliquée et théorique portant sur les écoles et les districts scolaires dans la mesure où elle pourra servir à étayer les programmes et les politiques visant l’amélioration des écoles, le rehaussement du rendement par les élèves et l’achèvement des études secondaires. Cet article présente les résultats récents d’une recherche en cours sur l’adaptation scolaire évaluée par le biais d’un questionnaire pluridimensionnel. Le questionnaire a d’abord servi d’outil pour un district scolaire canadien qui cherchait à mieux comprendre les raisons du décrochage scolaire. Depuis, le projet s’est transformé en collaboration impliquant plusieurs organisations. Cette étude révèle des associations systématiques entre l’adaptation des élèves à l’école, le rendement académique et l’achèvement des études secondaires. Elle milite en faveur de l’intégration de composantes non cognitives importantes au sein des systèmes scolaires d’information et d’évaluation.